ISOLASI DAN PEMURNIAN WEDELOLAKTON DARI TUMBUHAN URANG ARING (Eclipta alba L. Hassk) - Trisna Yuliana (Jurnal Kimia Terapan Indonesia, 2013)
Wedelolactone has a wide range of biological activities and used for the-treatment of various ailment. In the present study an experiment of isolation method of wedelolactone from Eclipta alba L. Hassk plant has been developed by conventional process using maceration method, partitions, and column chromatography and the result was characterized by NMR, UV- Vis and mass spectroscopy. The experimental results showed that the process of isolation isproduce wedelolactone with94% purity which are expected to be used as a standard.